Extracellular Signal-Regulated Kinase 1 Alone Is Dispensable for Hyperoxia-Mediated Alveolar and Pulmonary Vascular Simplification in Neonatal Mice - Renuka T. Menon; Shyam Thapa; Amrit Kumar Shrestha; Roberto Barrios; Binoy Shivanna (MDPI AG, 2022)
Bronchopulmonary dysplasia (BPD) is a morbid lung disease distinguished by lung alveolar and vascular simplification. Hyperoxia, an important BPD causative factor, increases extracellular signal-regulated kinases (ERK)-1/2 expression, whereas decreased lung endothelial cell ERK2 expression reduces angiogenesis and potentiates hyperoxia-mediated BPD in mice. However, ERK1's role in experimental BPD is unclear. Thus, we hypothesized that hyperoxia-induced experimental BPD would be more severe in global ERK1-knockout (ERK1-/-) mice than their wild-type (ERK1+/+ mice) littermates. We determined the extent of lung development, ERK1/2 expression, inflammation, and oxidative stress in ERK1-/- and ERK1+/+ mice exposed to normoxia (FiO2 21%) or hyperoxia (FiO2 70%). We also quantified the extent of angiogenesis and hydrogen peroxide (H2O2) production in hyperoxia-exposed neonatal human pulmonary microvascular endothelial cells (HPMECs) with normal and decreased ERK1 signaling. Compared with ERK1+/+ mice, ERK1-/- mice displayed increased pulmonary ERK2 activation upon hyperoxia exposure. However, the extent of hyperoxia-induced inflammation, oxidative stress, and interrupted lung development was similar in ERK1-/- and ERK1+/+ mice. ERK1 knockdown in HPMECs increased ERK2 activation at baseline, but did not affect in vitro angiogenesis and hyperoxia-induced H2O2 production. Thus, we conclude ERK1 is dispensable for hyperoxia-induced experimental BPD due to compensatory ERK2 activation.